Pengaruh Motivasi Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Di Lingkungan Komisi Pemilihan Umum Kabupaten Pesisir Barat - Merduani, Bisri; Salim (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2017)
The purpose of this study is to determine the effect of work motivation and organization culture toward employee performance at lingkungan Komisi Pemilihan Umum Kabupaten Pesisir Barat. The method used in this research is descriptive quantitative research with 55 research respondents. Based on the results of this study it can be concluded that 33,9% toward employee performance is influenced by work motivation. Influence of organization culture toward employee performance is 30,8%. Influenced of work motivation and organization culture toward employee performance is 35,1%.